'Melatonin isomer' in wine is not an isomer of the melatonin but tryptophan‐ethylester. Issue 4 (13th October 2014) - Gardana, Claudio; Iriti, Marcello; Stuknytė, Milda; De Noni, Ivano; Simonetti, Paolo
Abstract Melatonin is a neurohormone, chronobiotic, and antioxidant compound found in wine and deriving directly from grapes and/or synthesized by yeast during alcoholic fermentation. In addition, a melatonin isomer has been detected in different foods, wine among them. The special interest for melatonin isomer related to the fact that it was found in greater quantities than melatonin and probably shares some of its biological properties. Despite this, its chemical structure has not yet been defined; although some researchers hypothesize, it could be melatonin with the ethylacetamide group shifted into position N1. Thus, the aim of our study was to identify the structures of the melatonin isomer. For this purpose, melatonin and melatonin isomer in Syrah wine were separated chromatographically by a sub‐2 μm particle column and detected by tandem mass spectrometry. The sample was then purified and concentrated by solid‐phase extraction, hydrolyzed with alkali or esterase, and substrates and products quantified by UPLC‐MS/MS. Moreover, melatonin, melatonin isomer, and their product ions were evaluated by high‐resolution mass spectrometry. The amount of melatonin isomer and melatonin in the wine was 84 ± 4 and 3 ± 0 ng/mL, respectively. In the solutions, containing diluted alkali or esterase, melatonin isomer was hydrolyzed in about 8 min. Correspondingly, tryptophan was detected, and its amount increased and reached the maximum concentration in about 8 min. Melatonin concentration was not affected by diluted alkali or esterase. The fragmentation pattern of melatonin isomer was different from that of melatonin but comparable to that of tryptophan‐ethylester. Finally, the so‐called melatonin isomer identity was verified by cochromatography with authentic standard of tryptophan‐ethylester.